The haunted mask - Stine, R. L. (New York : Scholastic, 1993)
A young girl purchases the most frighteningly lifelike Halloween mask and then, to her horror, discovers that she is unable to remove it from her face.
"An Apple paperback."
4-6
580
Accelerated Reader AR
Keywords: Horror tales; Masks -- Fiction; Halloween -- Fiction